Aplicación del módulo educativo "Mi nuevo ser", para mejorar la autoestima de las gestantes del hospital I Essalud Moyobamba. Octubre 2003 Marzo 2004 - Apaestegui Huanca, Liz Hermelinda (2004)
In order to evaluate the improvement of self-esteem of pregnant hospital I Essalud Moyobamba by applying the Educational Module "My New Being," a quasi-experimental applied research was conducted, it was executed during the months of October 2003 to in March 2004. We worked with 60 pregnant women divided into two groups: an experimental group (A) and the control group (B), each with 30 pregnant. The experimental group "A" an educational module (Annex 3) that aimed to improve the self-esteem of pregnant applied. The group "B" will be offered only traditional lectures which are commonly offered on site. Gestational age in both groups ranged between I and II trimester in both groups was applied pre and post test, which measured the self-esteem of pregnant women before and after application of educational module. Finally five pregnant women in the experimental group depth interview which allowed us to determine the perception of the course name was applied. The results show that we have: self-esteem levels of pregnant women in the educational module was applied increased from 26.30 points (pretest) to 35.2 points (post test) on average. The "My New Being" educational module significantly improved self-esteem in pregnant women in the experimental group. It's interesting how some pregnant expressly state as he improved his personal acceptance and their relationship: my relationship is beautiful enough has improved because my pregnancy was a bit dific11pero through workshops I attended every week was a reason for talk more among us. "(primigravida, 17)" now talked more with my husband and we understand better very good, but after the course has changed and improved a lot because now I can talk more with my husband no better communication received through workshops. "(multfgesta, 34. based on the results obtained, the educational module" My New Being "has been validated as a technical tool that improves self-esteem in pregnant I Essalud Moyobamba hospital.